Implementation of Wedding Party Before Marriage Contract in the Perspective of Maqasid Sharia (Case Study in Gayo Lues Regency): Pelaksanaan Walimatul ‘Urs Sebelum Akad Nikah Dalam Tinjauan Maqashid Syariah (Studi Kasus di Kabupaten Gayo Lues) - Husnul, Muhammad; Maulina, Nurul (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2024)
Walimatul 'urs, or wedding feasts, as stipulated in hadith, should be conducted after the marriage contract (akad nikah) has taken place. This indicates that the marriage contract is prioritized over the walimatul 'urs. However, there are segments of society in Gayo Lues Regency that hold the walimatul 'urs prior to the marriage contract. This practice, as previously explained, contradicts the hadith. Furthermore, some scholars argue that walimatul 'urs should be conducted after the marriage contract and the consummation (dukhul) has occurred. This implies that both the marriage contract and consummation should be viewed and executed cumulatively. This study aims to examine the implementation of walimatul 'urs before the marriage contract according to Islamic law. Additionally, the analysis is conducted using a maqasid sharia approach. The research employs a qualitative method, utilizing field research. Primary data is obtained through interviews and observations conducted by the researcher. The findings indicate that the implementation of walimatul 'urs before the marriage contract contradicts the hadith, as the essence of marriage lies in the marriage contract, not in the walimatul 'urs. However, from the perspective of maqasid sharia, particularly the principle of hifzul mal (preservation of wealth), if walimatul 'urs is not prioritized, it may lead to dharar (harm). Since dharar must be eliminated, it can permit actions that are fundamentally prohibited or haram. Based on the considerations of maqasid sharia, prioritizing walimatul 'urs in this context is deemed more appropriate than prioritizing the marriage contract.